Genetic characterization of dogs via chromosomal analysis and array-based comparative genomic hybridization (aCGH) - Müller, M. H.; Reimann-Berg, N.; Bullerdiek, J.; Murua Escobar, H. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2012)
The results of cytogenetic and molecular cytogenetic investigations revealed similarities in genetic background and biological behaviour between tumours and genetic diseases of humans and dogs. These findings classify the dog a good and accepted model for human cancers such as osteosarcomas, mammary carcinomas, oral melanomas and others. With the appearance of new studies and advances in canine genome sequencing, the number of known homologies in diseases between these species raised and still is expected to increase. In this context, array-based comparative genomic hybridization (aCGH) provides a novel tool to rapidly characterize numerical aberrations in canine tumours or to detect copy number aberrations between different breeds. As it is possible to spot probes covering the whole genome on each chip to discover copy number aberrations of all chromosomes simultaneously, this method is time-saving and cost-effective – considering the relation of costs and the amount of data obtained. Complemented with traditional methods like karyotyping and fluorescence in situ hybridization (FISH) analyses, the aCGH is able to provide new insights into the underlying causes of canine carcinogenesis.
Keywords: Chromosomes; tumours; array-based comparative genomic hybridization